Programming With Varying Dietary Fat Content Alters Cardiac Insulin Receptor, Glut4 and FoxO1 Immunoreactivity in Neonatal Rats, Whereas High Fat Programming Alters Cebpa Gene Expression in Neonatal Female Rats - Govindsamy, Annelene; Ghoor, Samira; Cerf, Marlon E. (Frontiers in Endocrinology, 2022)
Fetal programming refers to an intrauterine stimulus or insult that shapes growth, development and health outcomes. Dependent on the quality and quantity, dietary fats can be beneficial or detrimental for the growth of the fetus and can alter insulin signaling by regulating the expression of key factors. The effects of varying dietary fat content on the expression profiles of factors in the neonatal female and male rat heart were investigated and analyzed in control (10% fat), 20F (20% fat), 30F (30% fat) and 40F (40% fat which was a high fat diet used to induce high fat programming) neonatal rats. The whole neonatal heart was immunostained for insulin receptor, glucose transporter 4 (Glut4) and forkhead box protein 1 (FoxO1), followed by image analysis. The expression of 84 genes, commonly associated with the insulin signaling pathway, were then examined in 40F female and 40F male offspring. Maintenance on diets, varying in fat content during fetal life, altered the expression of cardiac factors, with changes induced from 20% fat in female neonates, but from 30% fat in male neonates. Further, CCAAT/enhancer-binding protein alpha (Cebpa) was upregulated in 40F female neonates. There was, however, differential expression of several insulin signaling genes in 40F (high fat programmed) offspring, with some tending to significance but most differences were in fold changes (≥1.5 fold). The increased immunoreactivity for insulin receptor, Glut4 and FoxO1 in 20F female and 30F male neonatal rats may reflect a compensatory response to programming to maintain cardiac physiology. Cebpa was upregulated in female offspring maintained on a high fat diet, with fold increases in other insulin signaling genes viz. Aebp1, Cfd (adipsin), Adra1d, Prkcg, Igfbp, Retn (resistin) and Ucp1. In female offspring maintained on a high fat diet, increased Cebpa gene expression (concomitant with fold increases in other insulin signaling genes) may reflect cardiac stress and an adaptative response to cardiac inflammation, stress and/or injury, after high fat programming. Diet and the sex are determinants of cardiac physiology and pathophysiology, reflecting divergent mechanisms that are sex-specific.